One new genus and species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae) from China - Wang, Tao; Huang, Jianhua; Shi, Fuming (Zootaxa, 2020)
In this paper, one new genus Paradoxitettigia gen. nov. is established and one new species Paradoxitettigia longicaudica sp. nov. is described. Furthermore, the morphological images of the new species are provided.